Gender, poverty, and disability in the National Action Plan for Food and Nutrition 2017-2019 of Indonesia and ways forward - Go, Ara; Ramani, Gayathri V.; Olney, Deanna K. (International Food Policy Research Institute, 2020)
Over the past two decades Indonesia has undergone a major economic transformation including reducing the poverty rate by more than half to a current level of about 10% and becoming the 10th largest economy in the world. However, as the fourth most populous nation, this means that about 25 million Indonesians are living below the poverty line and even more are at-risk of falling into poverty. Although Indonesia’s economic growth has been impressive, indices related to human development and inclusion indicate that there is room for improvement. Across several indices, Indonesia is ranked in the bottom third to the bottom half of all countries.